Analysis of Geosites and Proposal for Expansion: Journey towards UNESCO Status for Călimani National Park - Vasilica Valentina Isopescu (Geoconservation Research)
The exploration and identification of new geosites in the Călimani Mountains region heralds a significant opportunity to establish Romania's first UNESCO volcanic geopark. This ambitious initiative aims to meticulously evaluate both natural and anthropogenic geosites across the area, highlighting their scientific, educational, and touristic significance, as well as their deep connections to the region's rich history and tradition. Utilizing an adaptation of the geosite analysis framework initially developed by Pralong, researchers in the country have tailored the methodology to better suit the Carpathian region. This study provides a detailed assessment of the criteria applied to the geosites in the Călimani Mountains, emphasizing their essential roles and underlining the need for their conservation through their integration into the Călimani National Park and the expansion of its boundaries. Through the quantitative and qualitative approach of this project, the goal is not only to protect and preserve these valuable geosites but also to promote them as sustainable and educational tourist resources.